Analisis Pengembangan E-Government di Pemerintahan Kota Tangerang - Cynthia, Cynthia; Warsono, Hardi; Mustam, Mochammad (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
This research describes and then to analyze how the development of E-Government program in Tamgerang of city government . This research uses descriptive qualitative research method. Based on the results of research, the development of E-Government program has not been well, because in the elements successful E-Government on capacity, where capacity it consists of the resources , human resources and technology .Three point that is still lacking if you really want to make E-Government in Tangerang be successful. Conclusion in this research is the lack of human resources so that the government Tangerang still need third party services. In addition, in gap also is weak, so that the availability of adequate technology could not yet be in achieving well. Based on conclusions, researchers recommended the government tangerang to do training to employees who handles E-Government program so that it creates employees are reliable.